2018
DOI: 10.1111/manc.12230
|View full text |Cite
|
Sign up to set email alerts
|

The North–South Divergence in Italy during theGreat Recession

Abstract: The economic recession that followed the 2007 crisis has widened the economic gaps between the wealthiest and the relatively poorer regions in Italy. The Great Recession has changed the importance of local economic strengths and hindered the possibilities of economic recovery, especially in the Mezzogiorno of Italy. We seek the local strengths present in Italian regions in the post-crisis period by comparing two macro areas to observe strong and weak points for intervention. A first analysis using multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 89 publications
3
2
0
Order By: Relevance
“…They are more geographically concentrated than both male-led converted companies and female-led companies in Italy. In general, our data suggest that companies located in the Center-North of the country have adopted a proactive approach to the crisis more than that located in the South; this finding is consistent with results obtained by Lagravinese (2015) and Odoardi and Muratore (2019) who analyzed the recessive period after 2009 in Italy and identified the greater difficulty of the southern regions of the country in reacting to the crisis.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…They are more geographically concentrated than both male-led converted companies and female-led companies in Italy. In general, our data suggest that companies located in the Center-North of the country have adopted a proactive approach to the crisis more than that located in the South; this finding is consistent with results obtained by Lagravinese (2015) and Odoardi and Muratore (2019) who analyzed the recessive period after 2009 in Italy and identified the greater difficulty of the southern regions of the country in reacting to the crisis.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…Overall, despite differences in size and population, the local communities involved in the study are afflicted by similar problems, such as high levels of unemployment and poverty, low quality of infrastructures, sluggish economy, and deteriorated labor productivity with an increasing number of young people leaving their home communities, decreasing levels of wellbeing and health (ISTAT, 2021). These major issues are consistent with the long‐term structural, economic, and social weakness of southern Italy (Odoardi & Muratore, 2019). At the same time, further challenges and opportunities are specific to this geographic area.…”
Section: Methodssupporting
confidence: 67%
“…Overall, despite differences in size and population, the local communities involved in the study are afflicted by similar problems, such as high levels of unemployment and poverty, low quality of infrastructures, sluggish economy, and deteriorated labor productivity with an increasing number of young people leaving their home communities, decreasing levels of wellbeing and health (ISTAT, 2021). These major issues are consistent with the long-term structural, economic, and social weakness of southern Italy (Odoardi & Muratore, 2019) Organization (WHO, 2018) has highlighted both the fast growth of the tourism sector due to the highly regarded natural and cultural heritage of the Apulia region as well as a significant level of quality of life among the resident population; at the same time, the WHO underlined the unemployment rate and the increasing number of people living on low incomes as serious issues posed to the territory's welfare policies.…”
Section: The Context Of the Studysupporting
confidence: 67%
“…As it has been shown that the population in Southern regions is more vulnerable to the precariousness created by informal work, 53 complaints were raised that the institutional response to the pandemic was skewed towards the interest of the North. This reflects historical patterns of structural regional inequality 65 , 66 and exacerbates politically-relevant perceptions of it. In this respect, a risk was also identified in the danger of organised crime’s acquisitions of struggling businesses in the wake of the pandemic, as part of widespread exploitation and money laundering operations in the South.…”
Section: Discussionmentioning
confidence: 82%